Game Pengenalan Tokoh Nasional Tan Malaka - Sutimin, Anugerahsurya Putrapradana; Tulenan, Virginia; Najoan, Xaverius B.N. (Jurnal Teknik Informatika, 2021)
Tan Malaka or Ibrahim Datuk Tan Malaka is the person who first wrote the concept of the Republic of Indonesia through his book Naar de Republiek Indonesia (Towards the Republic of Indonesia) and was nicknamed the Father of the Republic by Muhammad Yamin. This book became the basis of the concept of the State of Indonesia which inspired Soekarno through his book Towards an Independent Indonesia. Game is a system or program in which one or more players make decisions through control of objects in the game for a specific purpose. The purpose of this research is to design and build a game to introduce the national character Tan Malaka using the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages, namely: Concept, Design, Material Collecting, Assambly, Testing, and Distribution. The result of this research is the introduction of the National Figure Tan Malaka game that can be played on a PC.